Upaya Guru Bimbingan dan Konseling Mengatasi Perilaku Prokrastinasi Akademik Siswa Pasca Pandemi Covid-19 - Rizki Assingkily; Mahidin Mahidin (Sekolah Tinggi Agama Islam Sumatera Medan, 2022)
Assignments are an important part of the learning process. However, students view the task as a burden, so that they often delay or even do not do the task on purpose, which is termed academic procrastination behavior. This study aims to analyze the efforts of guidance and counseling teachers in overcoming students' academic procrastination behavior. The focus of this research is aimed at students at MAN 1 Aceh Tenggara with a post-Covid-19 pandemic setting to review the differences from the Covid-19 pandemic era. The research approach uses qualitative case study method. Obtaining data through participant observation techniques, in-depth interviews and documentation studies. The results of this study concluded that the counseling teacher's efforts to overcome academic procrastination behavior in students at MAN 1 Aceh Tenggara were carried out effectively. This is marked by two actions, namely preventive measures and counseling services. As for prevention in the form of classical guidance, groups, and the provision of individual guidance services to students. While counseling services in the form of educative sanctions for troubled students and appreciation for the success of students completing assignments on time. This research has implications for improving students' attitudes, especially in participating in learning.